2009
DOI: 10.1111/j.1469-8749.2009.03300.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and adaptive skills in myotonic dystrophy type 1: a study of 55 individuals with congenital and childhood forms

Abstract: Aims  To investigate cognitive abilities and adaptive skills in children and adolescents with myotonic dystrophy type 1 (DM1) and correlate the findings to the cytosine‐thymine‐guanine (CTG) repeat expansion size. Method  Cognitive level was assessed in 55 children and adolescents with DM1 (31 males, 24 females; mean age 12y 1mo, SD 5y 1mo; range 2y 7mo–21y 5mo) divided into the following categories: severe congenital DM1 (n=19), mild congenital DM1 (n=18), and childhood DM1 (n=18). The Griffiths Mental Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 22 publications
7
68
1
3
Order By: Relevance
“…While intellectual impairment and oral facial weakness have been previously reported, this study further evaluates the disease burden associated with CDM. 7,8,10 Specifically, we provide evidence of daytime sleepiness and motor delay that have not been previously reported. The outcome measures used in the study were chosen based on past pilot studies by the authors, recent patient-reported disease burden, and relevant literature focusing on CDM and other pediatric neuromuscular disorders.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…While intellectual impairment and oral facial weakness have been previously reported, this study further evaluates the disease burden associated with CDM. 7,8,10 Specifically, we provide evidence of daytime sleepiness and motor delay that have not been previously reported. The outcome measures used in the study were chosen based on past pilot studies by the authors, recent patient-reported disease burden, and relevant literature focusing on CDM and other pediatric neuromuscular disorders.…”
Section: Resultssupporting
confidence: 56%
“…Both intellectual impairment and oral facial weakness cause significant burden during childhood. 7,8 In addition to intellectual impairment, there is evidence of autism spectrum disorder and attention-deficit/hyperactivity disorder. 7,9 A prior cross-sectional survey study identified difficulty with communication and problems with hands and fingers as the issues that reduce quality of life in children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other systems commonly affected are the heart, lungs, smooth muscle, endocrine regulation, and brain [1]. Developmental delay and learning disabilities of varying degrees, are common in the congenital and childhood forms of the disease and the prevalence of neuropsychiatric disorders is higher in this group than in the general population [2,3]. DM1 has an autosomal dominant inheritance pattern and is caused by an expansion of a CTG-repeat sequence (trinucleotide expansion) on chromosome 19q13.…”
Section: Introductionmentioning
confidence: 99%
“…Ved debut senere er det ofte atferdsvansker og laerevansker som først gjør seg gjeldende (16). Selv om en diagnostisk gentest er lett tilgjengelig, kan det gå lang tid før riktig diagnose blir stilt og barna blir forstått på riktig måte.…”
Section: Dystrophia Myotonica Typeunclassified